Effect of different particle-size biochar on methane emissions during pig manure/wheat straw aerobic composting: Insights into pore characterization and microbial mechanisms. (November 2018) - He, Xueqin; Yin, Hongjie; Sun, Xiaoxi; Han, Lujia; Huang, Guangqun
Graphical abstract: Highlights: Effects of rice straw biochar (RSB) on manure composting were investigated. Addition of powdered RSB caused methane emissions to increase by 56.84%. Addition of granular RSB caused methane emissions to decrease by 22.15%. Granular RSB increased both the pore volume and connectivity of initial samples. RSB reduced the methanogen to methanotroph ratio in initial samples. Abstract: This study explored the effects of different particle sizes of rice straw biochar (RSB) on the methane emissions of pig manure/wheat straw aerobic composting experiments to provide a theoretical suggestion for biochar application. The experiments were conducted with a control group, powder (<1 mm) group, and granular (4 mm–1 cm) group. Methane emissions increased by 56.84% in the powder group but decreased by 22.15% in the granular group during the aerobic composting. Methane was generated by methanogens and methanotrophs in the specific anaerobic micro-environment characterized by X-ray micro-computed tomography (micro-CT). The porosity of initial composting samples increased by 4.02% in the granular group but decreased by 3.88% in the powder group. RSB additives typically reduced the mcrA/pmoA ratio and increased the diversity of Bacteria and Archaea. Conclusively, granular biochar benefits to aerobic composting to alleviate the CH4 emissions.